Bangkitnya Perekonomian Indonesia Pasca Covid-19 - M.E, Rusmini,; Nur Cahyono , Dimas; Putri, Kristina; Afkarina, Izza; Aprilia, Puput; Taufiq, Achmad; Puji Lestari, Devi; Junisa Silvia, Khofifah; ., Misrul; Aldio Firmanda, Bagus (Universitas Sahid Surakarta, 2023)
The Indonesian economy is the largest economy in Southeast Asia and one of the developing market economies. However, during the Covid-19 pandemic, the economy experienced a downturn. Befor the Covid-19 pandemic, Indonesia's economic conditions were still showing positive growth and that globally, and not only globally, the Indonesian economy was even before the Covid-19 pandemic, nationally it was still quite good in terms of the JCI in early January which had touched the figure around 6300 this is a good and interesting achievement for Indonesia. However, along with the arrival of the Covid-19 pandemic in Indonesia, resulted in the paralysis of some activities in Indonesia, especially in the field of economic growth. So that with the arrival of the pandemic, the national economy experienced a decline in the JCI, which was originally around 6300 before the pandemic, during the pandemic the JCI fell to around below the 4000 level.